2020
DOI: 10.5935/1518-0557.20200061
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between age and blastocyst chromosomal ploidy analyzed by noninvasive preimplantation genetic testing for aneuploidies (niPGT-A)

Abstract: Objective: To assess the relationship between human blastocyst chromosomal ploidy established by niPGT-A and increasing age. Methods: This is a prospective multicenter study carried out by ten assisted reproduction centers after their embryologists acquired training and validated their results with the previous use of niPGT-A. A total of 94 couples with indication for niPGT-A due to increase maternal age, male factor, repeated implantation failures, recurrent abortion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Nevertheless, in this study, patients’ ages in the cycles with 2.1PN zygotes were higher than those without 2.1PN zygotes, and the two patients with mosaic embryos were relatively young (30 and 32 years). Although it has been reported that chromosomal aneuploidy is associated with age, 20 , 21 , 22 , 23 further research is required to gain a more complete understanding of whether the aneuploidy of 2.1PN embryos is associated with patient age.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in this study, patients’ ages in the cycles with 2.1PN zygotes were higher than those without 2.1PN zygotes, and the two patients with mosaic embryos were relatively young (30 and 32 years). Although it has been reported that chromosomal aneuploidy is associated with age, 20 , 21 , 22 , 23 further research is required to gain a more complete understanding of whether the aneuploidy of 2.1PN embryos is associated with patient age.…”
Section: Discussionmentioning
confidence: 99%
“…Vagini et al (2020) usando PGT-A relacionaron la edad con aneuploidías, viendo incrementada su prevalencia y reportando el síndrome de Klinefelter como la cromosomopatía más frecuente (18/71 [25%]) 16 . Kroener et al (2012) analizando blastocistos D5 y todos aquellos con desfase de al menos 24 horas (mórulas D5 y D6, blastocistos D6), evaluaron el grado morfológico, reportaron que los que tuvieron un desfase de 24 horas no mostraron una diferencia significativa en presentar aneuploidías, sin embargo, le dieron mayor importancia al grado morfológico; es decir, un embrión óptimo, independientemente del día de desarrollo, tiene altas posibilidades de ser euploide 17 .…”
Section: Discussionunclassified
“…The majority of “mosaic” results indicated high-level mosaicism, which may relate to the process and purpose of embryonic self-correction mechanisms. Similar to invasive PGT-A, mosaicism did not vary depending on maternal age, while aneuploidy levels had a positive correlation with maternal age [ 109 ]. In another recent study, SCM niPGT-A results were also investigated relevant to pregnancy outcome, and live births were associated with low embryonic cfDNA in SCM [ 70 ].…”
Section: A Look Into the Strategies Employed For Nipgtmentioning
confidence: 99%